Power System Implications of Subsidy Removal, Regional Electricity Trade, and Carbon Constraints in MENA Economies - Timilsina, Govinda R. (World Bank, Washington, DC, 2020)
This study analyzes impacts on the power sector in the Middle East and North Africa region of three policies: removal of fuel subsidies, cross-border electricity trade, and reduction of carbon dioxide emissions in line with commitments under the Paris Agreement. The analysis uses a power system planning model that minimizes the total electricity supply cost over 2018–35 by satisfying specified technical, economic, environmental, and policy constraints. The study shows that the region would save between US$26.3 billion and US$27.5 billion, measured in 2018 prices, by removing subsidies of natural gas used for power generation. It would save US$83.6 billion to US$90.9 billion through cross-border electricity trade. The two policies together would yield a reduction of 10 percent in cumulative power sector carbon dioxide emissions in the region, with a net cost savings of US$111 billion. If a carbon constraining policy is considered to achieve the same level of reduction of emissions, the cost of the power system would increase by US$97 billion. The study also reveals that the benefits of subsidy removal would be higher in the presence of cross-border trade, and the benefits of cross-border trade would be higher in the absence of fuel subsidies.